Tityus lourencoi, a new species of scorpion from the Cordillera Oriental, Colombia (Scorpiones: Buthidae) - Florez D., Eduardo (1996)
Tityus lourencoi, a new species of scorpion belonging to the Tityus melanostictus group of species is described from Quetame, Department of Cundinamarca, in the Cordillera Oriental of Colombia.The new species is associated to Tityus melanostictus Pocock and Tityus engelkei Pocock, but can be distinguish from the first by rnorphometric values, and from the second by a srnaller number of pectinal teeth